The effects of childbearing on women's body mass index, and on the risk of diabetes mellitus, or ischaemic heart disease after the menopause - Bobrow, K; Kirsten Bobrow (2012)
Background: Excess adiposity, diabetes mellitus, and ischaemic heart disease are common important causes of morbidity and premature mortality in postmenopausal women in the UK. A large amount of data exists on known risk factors for these conditions, and for risk factors men and women share there is little evidence to suggest sex-based differences. It has been suggested that factors unique to women (such as parity and breastfeeding) may also influence risk. The nature of the relationship between childbearing and these conditions remains to be clarified. In this thesis I explore the association between women’s childbearing histories and their adiposity, and risk of diabetes or ischaemic heart disease after the menopause, to provide evidence on the character, repeatability and public health relevance of the associations. Aim: To explore the hypothesis that childbearing (specifically parity and breastfeeding) is associated with women’s body weight and risk of excess adiposity, and also with women’s risk of diabetes mellitus, and ischaemic heart disease after the menopause. Methods: Data are analysed from a large population-based cohort of middle-aged UK women recruited in 1996 to 2001 (the Million Women Study) with complete childbearing information, and who had baseline anthropometry, and were followed for incident diabetes or ischaemic heart disease through repeat survey questionnaires, hospital admission records, and central registry databases. Results: In a large ethnically homogeneous population of postmenopausal UK women increasing parity was associated with an increase in BMI, however this increase was offset in women who breastfed. The associations between parity, breastfeeding and BMI were of a similar order of magnitude to established risk factors known to be associated with BMI, for example smoking, and physical activity. The associations between childbearing and women’s risk of diabetes mellitus after the menopause appear to be largely due to the effects of childbearing on maternal BMI. There is only limited evidence to suggest a direct effect of childbearing on women’s risk of diabetes after the menopause. There is statistically significant evidence of an association between childbearing and women’s risk of ischaemic heart disease after the menopause. Parity was associated with a modest increase in risk whereas breastfeeding was associated with a small decrease in risk, however the effects were small in comparison to known important risk factors. Conclusions In a large population of UK women childbearing was found to have a persistent influence on women’s mean BMI after the menopause, and through this postmenopausal risk of diabetes mellitus. Childbearing was also found to be mod-estly associated with women’s risk of ischaemic heart disease after the menopause.